SUSTAINABLE DEVELOPMENT GOALS IN MIDDLE SCHOOL SCIENCE CURRICULUM - Dabas, Manisha Wadhwa Nee; Singhal, Mamta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Sustainable Development Goals (SDGs) are a set of 17 goals adopted by all United Nations (UN) member nations in 2015, aiming to achieve "peace and prosperity for people and the planet" by 2030, addressing issues like poverty, inequality, and climate change. It is one of the most significant agenda of policymakers, scientists, environmentalists and educationists all over the world. These goals provide a roadmap for a better and sustainable future for everyone. However, unless a common citizen is made aware of these goals and is equipped to take positive actions towards achieving them, we cannot hope to realize them in the near future. The education system has the potential as well as the responsibility for preparing the young minds to become torch bearers of the Sustainability Agenda-2030. The paper discusses the role of science education in this context. The main objectives include: (i) To locate the representation of SDGs in middle school science textbooks written post NCF-2005. (ii) To explore teachers' understanding of SDGs and pedagogical approaches used by them in classrooms with a specific focus on their relevance to sustainable development issues and practices. The findings of this research have implications for curriculum and textbooks for middle school in the light of National Education Policy (NEP) 2020.